Bioconversion of agro-food industrial wastes into value-added peptides by a Bacillus sp. Mutant through solid-state fermentation. (February 2022) - Tuly, Jamila A.; Zabed, Hossain M.; Nizami, Abdul-Sattar; Mehedi Hassan, Md; Roknul Azam, S.M.; Kumar Awasthi, Mukesh; Janet, Quaisie; Chen, Gu; Dzidzorgbe Kwaku Akpabli-Tsigbe, Nelson; Ma, Haile
Graphical abstract: Highlights: Chicken feather powder (CFP) and okara were valorized by solid-state fermentation (SSF). CFP and okara composites were converted to peptides by a mutant Bacillus licheniformis . A ratio of Okara to CFP of 7:10 produced 185.99 mg/g peptides after 90 h SSF. The keratinase activity was 910.12 U/g with 85.03% antioxidant activity. Abstract: Advances in microbial enzyme technology offer a significant opportunity for developing low-energy bioconversion solutions for industrial wastes as inexpensive feedstocks for useful products. In this short communication, two agro-food industrial wastes, chicken feather powder (CFP) and okara, were converted into peptides by a Bacillus licheniformis mutant using solid-state fermentation (SSF). The optimum SSF conditions for okara to CFP ratio, inoculum size, and time were 0.7 (7:10), 15%, and 90 h, respectively, which produced 185.99 mg/g peptides, with 910.12 U/g keratinase activity and 85.03% antioxidant scavenging activity. Compared to okara, CFP with mutant strain showed 11.28% higher keratinase activity and produced higher amounts of peptides (5.51%).